Pengaruh Pengungkapan Elemen-Elemen Integrated Reporting terhadap Nilai Perusahaan pada Perusahaan Properti dan Real Estate Tahun 2019-2022 - Irfansyah, Muhammad Eddy; Hifni, Syaiful (Universitas Darwan Ali, 2025)
This study aims to examine the effect of integrated reporting element disclosures on firm value in property and real estate companies listed on the Indonesia Stock Exchange during the period 2019–2022. The sampling technique used was purposive sampling, and 22 companies were selected as the sample. The results show that the disclosure of the business model element and performance element has a significant negative effect on firm value, while the remaining elements have no significant impact. These findings indicate that the disclosure of elements in integrated reports has not yet had a meaningful influence on firm value in Indonesia. This could be due to the low quality of disclosures, limited investor understanding of non-financial information, and the fact that the market is still developing. These findings should serve as a point of evaluation for companies and stakeholders to improve the relevance of integrated reporting. Companies need to enhance the quality of disclosures by avoiding general, normative, and irrelevant narratives. It is recommended that companies present a more consistent and logical connection between strategy, business model, risks, and performance. When disclosing elements such as risks, future outlook, and resource allocation, companies should include quantitative indicators and impact assessments. Companies must also maintain a balance in transparency, especially when reporting on performance and risk elements.